Formation of the university electronic information-educational environment: interaction, development of professional thinking, management - I. V. Serafmovich; O. M. Кonkova; A. V. Raykhlina (Открытое образование (Москва))
Purpose of the research. The development of electronic technologies in modern socio-economic environment and the urgent need for their integration into higher education require a different type of teachers’ professional thinking based on their sustainable self-development. The paper provides a reflexive analysis of the implementation of electronic information-educational environment (EIEE) by the Yaroslavl branch of Plekhanov Russian University of Economics and offers an insight into interactive and management aspects of EIEE integration and use in the educational process.Materials and methods. To achieve the goal, the EIEE structural and functional components were identified, stages, system requirements and technical features of EIEE implementation were determined along with the prospects for EIEE further integration and development within the university. Analysis, synthesis, comparison and generalization approaches were used as general scientific methods of this research.Results. The paper gives an insight into the project of the Yaroslavl branch of Plekhanov Russian University of Economics on the use of EIEE as an imperative for high-level development of graduates’ common cultural, as well as general and specific professional competencies, to facilitate their competitiveness in the labour market. The urgency of innovations in the EIEE integration in universities is substantiated. The authors emphasize that the EIEE practical application requires achievement of a new level of communication skills, interaction of all participants in the educational process, based on a broader vision of the educational environment and a new level of teachers’ professional thinking, presupposing both creativity and management of their own mental processes associated with metacognition.Conclusion. As a result, the authors make conclusions on the implementation of various aspects of the university EIEE, such as administrative, managerial and interactive ones. According to the study, a wide application of EIEE can become a priority tool in solving problems of the effectiveness, which is proved by the evidence and examples from the educational experience given in the article.